A Critical Study about the Human Rights Concerns in the Kashmir Valley - Taha Shabbir; Zafar Ali; Shuja Uddin; Mohsin Wazir; Muhammad Ali Gopang (HUMAN: South Asian Journal of Social Studies, 2021)
While the United Nations is authorized to impose final remedies in Kashmir, it has limited itself to making recommendations in the hope of achieving a just and impartial settlement acceptable to all parties to the dispute. This thesis will do an observational examination of the different proposals, utilizing this accurate and positivist assessment of the United Nations' behavior as a case study. To resolve the Kashmir situation, the Security Council must substantiate the following hypothesis: Any decision or omission took by the United Nations Security Council was motivated by a desire to maintain a negotiated stalemate between India and Pakistan, a kind of status quo, before all remaining issues, whether factual or legal, are settled by direct negotiations between the two disputing parties. The United Nations took action after concluding that it could not resolve the issues under the circumstances, partly due to the conflicting positions and aspirations of the Kashmir dispute's parties and partly due to the UN system's shortcomings. From a positivist perspective, this study will aim to include an empirical examination of the United Nations' actions in settling an international dispute. It will assist in dispelling common misconceptions regarding the United Nations' status, which I assume are the product of an excessively positive or overly pessimistic appraisal of the UN's capacity and belief of its own will to enact a specific solution situation. I will attempt to explain in the concluding chapter of this study why I believe the United Nations is vital to global security, including in its handling of the Kashmir dispute. I am well aware that scholars and leaders in India and Pakistan will almost certainly cast doubt on my primary theory. This is fair since their active involvement in the issue will easily skew their perception of the UN's role. All also threatened the UN with a rejection of